Penggunaan Pupuk Organik untuk Meningkatkan Hasil Tanaman Cabai Kelompok Tani di Kabupaten Minahasa - Jacklin Stella Salome Manoppo; Ernest Hanny Sakul; Marlina Karundeng (DEDIKASI, 2018)
After doing observations and surveys in Paslaten Village, Remboken District, it was found that manyfields or former rice fields which are no longer effective by the owner's farm. Therefore, the fields become idle landand have the potential to be no longer productive, and currently only become a place to bind livestock. Moreover,there are many wastes, especially organic waste as a result of the daily activities of community life in PaslatenVillage. One type of organic waste found is chicken manure, which if it is not reused, it will cause an environmentalpollution. Thus, it is better to manage the waste into organic fertilizer. Paslaten Village, Remboken District, thereare Masawangan and Pinaesaan farmer groups who have tried to plant chili plants in the traditional way according tothe local wisdom in their village. Nevertheless, the production of chili crops is still lacking. As a result, a training isneeded to be carried out in order to increase the production of chili crops. The necessity for the application ofagricultural technology that is required by this farmer groups is the use of effective microorganisms (EM4) asbiological agents that can accelerate the decomposition process of chicken manure into quality organic fertilizer. Itis combined with black silver plastic mulch technology and integrated pest control using bio-pesticides, with a targetto increase the production and quality of chili plants. The first crop yield which was obtained by the farmer groupswas Nirmala variety chili. It has sharp fruit, 4 x 0.8 cm, spicy, shiny red color and can be harvested at the age of 80-85 days after planting (DAP). The average weight of chili per plants are 0.5 - 1.0 kg per plant, with weights per fruitranging from 2-3 grams and potential crops are 8-12 tons/ ha.